HUBUNGAN POLA ASUH ORANG TUA DAN PERKEMBANGAN BALITA DI POSYANDU FLAMBOYAN KELURAHAN RUNGKUT MENANGGAL SURABAYA - Dzihni Waida Atika Putri, NIM011611223047 (2018)
Background: parenting is one of the environmental factors that affect the development of toddlers. There are three kinds of parenting, that permissive, democratic and authoritarian parenting. A toddler who got the predictable democratic parenting can avoid aberration progression. Therefore, it is very important for parents not to apply other than democratic parenting. The clinic is one of the Gunung Anyar public health care in Surabaya, and the last 2 years there are some toddlers who experience developmental delays or irregularities (the year 2016 of 0.80% and the year 2017 of 1.20%). The purpose of this research is to analyze the relationship of parenting parents and toddler development at Posyandu Flamboyant Rungkut Menanggal Surabaya. Methods: this research is a type of observational analytic study with cross-sectional. The sample in this research is children aged 12-60 months at Posyandu Flamboyant Rungkut Menanggal Surabaya that meet the criteria for inclusion and exclusion. Sampling technique is using the method the total sampling, and a large sample of 55 respondents. Its independent variable is a pattern of foster parents, and the dependent variable is the development of toddlers. The instruments use Questionnaire Pre Screening Research and Development. Data analysis technique is using spearman with α = 0.05 and analysis of the relationship two variables with correlations. Results: the obtained value p 0.01 and the correlation coefficient 0.343. It shows significant association between parenting parents and toddler development, and has the strength of weak ties (0.20 < KK < 0,40). Conclusion: the role of parents is vital in shaping the personality of the child where the parent is expected to deliver his son reach the development stage of age appropriate. Keywords: Development, Parenting, Toddler